2010
DOI: 10.1099/mic.0.039040-0
|View full text |Cite
|
Sign up to set email alerts
|

Role of Hfq in iron-dependent and -independent gene regulation in Neisseria meningitidis

Abstract: In Neisseria meningitidis, iron-responsive gene regulation is mediated primarily by the ferric uptake regulator (Fur) protein. When complexed with iron, Fur represses gene expression by preventing transcription initiation. Fur can also indirectly activate gene expression via the repression of regulatory small RNAs (sRNA). One such Fur- and iron-regulated sRNA, NrrF, was previously identified in N. meningitidis and shown to repress expression of the sdhA and sdhC genes encoding subunits of the succinate dehydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 36 publications
1
47
0
Order By: Relevance
“…These findings extend our knowledge of the whole transcriptome of N. meningitidis; previously, other research groups had shown the expression in N. meningitidis of small regulatory RNAs with a role in bacterial pathogenesis (14,35,38), and proteomic and transcriptomic analysis of Hfq deletion mutants suggested the presence of a small-RNA network in the bacterium (13,36,45). Here, we reported a panel of expressed small RNAs that could be involved in the adaptation of N. meningitidis to the human blood environment.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…These findings extend our knowledge of the whole transcriptome of N. meningitidis; previously, other research groups had shown the expression in N. meningitidis of small regulatory RNAs with a role in bacterial pathogenesis (14,35,38), and proteomic and transcriptomic analysis of Hfq deletion mutants suggested the presence of a small-RNA network in the bacterium (13,36,45). Here, we reported a panel of expressed small RNAs that could be involved in the adaptation of N. meningitidis to the human blood environment.…”
Section: Discussionsupporting
confidence: 83%
“…Moreover, an antisense transcript for prpB and prpC was detected (Fig. 3B), and the PrpB and PrpC proteins were deregulated in an Hfq deletion mutant (13,36,45).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Hfq-dependent repression of prpB expression was subsequently shown to be mediated by two trans-acting sRNAs, RcoF1 and RcoF2 [27]. Northern blot analysis revealed that both the single prpB and the bicistronic prpB-prpC mRNAs were up-regulated upon the deletion of hfq or a double deletion of rcoF1 and rcoF2 [28], thereby confirming the genetic link between RcoF1/2, Hfq and prp gene expression. By regulating prpB, RcoF1 and RcoF2 appear to be the first trans-acting sRNAs with a direct host-associated function in N. meningitidis [27].…”
Section: Other Regulators Of Prp Gene Expressionmentioning
confidence: 73%
“…The sRNAs, RyhB of Escherichia coli and Vibrio cholerae (42), PrrF1 and PrrF2 of Pseudomonas aeruginosa (53), FsrA of Bacillus subtilis (29), and nrrF in Neisseria meningitidis (43,44) were found to be repressed by iron-bound Fur, indicating that the target genes of these small RNAs were indirectly activated by Fur. In Salmonella enterica serovar Typhimurium, Fur represses a repressor protein, the histone-like nucleoid structuring protein (H-NS), which negatively regulates hilA, resulting in indirect activation of hilA by Fur (52).…”
mentioning
confidence: 99%